Pengaruh Opinion Shopping, Financial Distress dan Audit Report Lag terhadap Penerimaan Opini Audit Going Concern - Ramadinda, Annisa Dwi; Mulyani, Erly (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to examine the effect of opinion shopping, financial distress and audit report lag on the acceptance of going concern audit opinions. This study uses quantitative methods to test the the ory and analyze the relationship between variables. The population in this study are consumer cyclicals sector companies listed on the Indonesia Stock Exchange for the period 2021-2023. This study uses purposive sampling, there are 58 companies over a 3-year period and produces 174 observation data. The analysis technique used in this study is logistic regression analysis. The results of the study with logistic regression analysis show that the variables opinion shopping, financial distress and audit report lag do not affect the acceptance of going concern audit opinions.